(untitled) (Cadernos de Psicologia Social do Trabalho, 2012)
The town of Santo Antonio do Monte is deemed to be the 2nd largest center of fireworks production in the world, and pyrotechnics is the region's main economic activity. However, the work in the pyrotechnic industry has raised serious concerns from labor unions and researchers, as well as the workers and their families. Labor accidents in this sector are usually fatal or mutilating, and there're also reports of labor-related diseases. Thus, this study aimed to analyze the repercussions of the fireworks production process on these workers' health and safety. Studies on the Psychopathology of Work and those based on the French tradition of ergonomic analysis provided the main references for this study. To carry out this research, we used a pluridimensional methodological strategy, which gathered and connected statistical, empirical (clinical facts, reports, observations), and documental data. The results show that workers are exposed to accidents resulting from the performance of jobs for which they haven't been properly trained, as well as to a painful and harmful activity, which causes repetitive strain injuries (RSIs) and workrelated musculoskeletal diseases. Women who work in this sector also face sexual harassment practiced by their employer's representatives.